Tracing hydrological and ecological dynamics in a volcanic barrier-lake system in NE Iberia during the Late Glacial–Early Holocene using non-pollen palynomorphs - Jordi Revelles; Eneko Iriarte; Francesc Mesquita-Joanes; Maria A. Rodrigo; Maria Saña (Review of Palaeobotany and Palynology, 2026)

Association of the endosomal TLR4 pathway with dorsolateral prostatic remodeling induced by perinatal phthalate mixture exposure in rats - Vinícius Luís Rocha da Silva Maria; Ana Clara Pacheco de Santana; Patrick Vieira Souza; Vanessa Aguiar Rocha; Matheus Naia Fioretto; Natália Magosso; Mirella Franco Moreira; Maria Clara Betete Da Silva Fonseca; André Mascarenhas Guariento; Sergio Pereira; Ariana Musa Aquino; Letícia P. Bomfim; et al. (Reproductive Toxicology, 2026)

Optimization of the production of biolubricants from a residual oil by a hydroesterification strategy: Yield-dependent performance evaluation of home-made combi-biocatalyst systems - Rodolpho R.C. Monteiro; Maria M.F. de Melo Neta; Adriano A. Mendes; F. Murilo T. de Luna; Roberto Fernandez-Lafuente; Rodrigo S. Vieira (Sustainable Chemistry and Pharmacy, 2026)

Flux Science Without Borders: Strengthening Ecosystem Flux Capacity in Latin America - Tonantzin Tarin; M. Susana Alvarado‐Barrientos; Eugenia González del Castillo; Mónica Cervantes‐Jiménez; Zulia Sánchez‐Mejía; Alejandro Cueva; Alejandro Delgado‐Guerrero; Dulce Flores‐Renteria; Jaime Garatuza‐Payan; César Hinojo‐Hinojo; Karem Meza; David J. P. Moore; et al. (Global Change Biology, 2026)
The future of how we understand and manage ecosystems largely depends on direct and continuous observations that connect local territories to planetary processes. Latin America (LATAM: Mexico, Central and South America, and the Caribbean) hosts ecosystems critical for regulating global carbon, water, and energy cycles. However, persistent underinvestment in science and technology hampers the long‐term monitoring capacity needed to advance regional priorities. Addressing the climate crisis requires investing in local researchers, technicians, and students, providing Earth System Science training that integrates biophysical and sociocultural knowledge. Although English is the lingua franca of science, training in native languages accelerates technical capacity, strengthens regional collaboration, and grounds solutions in local experience. Here, we present TAFE ( Taller de Aprendizaje de Flujos Ecosistémicos ) as an example of how regionally grounded, native‐languages training can strengthen ecosystem flux science in LATAM and beyond. Such initiatives help decentralize knowledge, reduce the underrepresentation of Global South ecosystems in flux databases, and empower the next generation to lead research for both regional and global benefit.

Spatial variability and source apportionment of particulate matter (PM2.5) in Rio de Janeiro: insights from Urban, preserved, and biomass burning areas - Luis Fhernando Mendonça da Silva; Hellen Gonçalves Vieira; Elizanne P. S. Justo; Ivan Víctor Silva Guillen; Rodrigo Stellet Ferreira; Vanessa A. dos Anjos; Ricardo Henrique M. Godoi; Maria Cristina Canela; Cibele Maria Stivanin de Almeida; Tatiana Dillenburg Saint’Pierre; Adriana Gioda (Journal of Atmospheric Chemistry, 2026)
Air pollution is a critical environmental issue influenced by both natural and anthropogenic sources. We hypothesized that PM 2.5 chemical composition varies spatially due to local anthropogenic sources, soil resuspension, and biomass burning. This study analyzed particulate matter (PM 2.5 ) concentrations and chemical composition (black carbon (BC), elements, and ions) in three locations in Rio de Janeiro state: Gávea (urban area), PARNASO (environmental preservation area), and Campos dos Goytacazes (urban with burning biomass). The results show that PM 2.5 concentrations varied significantly among the sampled sites, with the average highest values recorded in PARNASO (20 ± 13 µg m − 3 ), followed by Gávea (12 ± 7 µg m − 3 ), and Campos (8 ± 4 µg m − 3 ). Although no daily samples exceeded Brazilian air quality standards, 23% surpassed WHO guidelines. Fe and Al were the most abundant elements in all sites, indicating strong soil resuspension influence, with higher concentrations in Campos. BC was higher in PARNASO (2.2 ± 0.9 µg m − 3 ) but contributed more to PM 2.5 in Campos (22–24%), highlighting the biomass-burning influence. Water-soluble ions, particularly Cl − , Na + , SO 4 2− , and NO 3 − , were predominant across all sites, with K + showing statistical differences between seasonality in Campos. A Principal Component Analysis (PCA) identified soil resuspension, vehicular emissions, and biomass burning as major contributors to PM 2.5 pollution. These findings underscore the necessity for region-specific air quality policies and continuous monitoring, emphasizing their global relevance for effective long-term pollution mitigation in urban, and preserved areas.

Short-term laboratory assessment of elevated temperature effects on two aquatic plants - Joanna Rosińska; Eric Puche; Maria A. Rodrigo (Aquatic Ecology, 2026)

Partitioning Soil Respiration: Differentiating Root Contributions and Environmental Factors - Wanderson Benerval de Lucena; Daniel Carlos Machado; Polyana Pereira; Maria Elisa Vicentini; José A. Neira Román; Glauco de Sousa Rolim; Alan Rodrigo Panosso; Newton La Scala (Agricultural Research, 2026)

Influence of agricultural residues on the formation of TiO2 phases: Real-time in situ X-ray diffraction monitoring in a reaction chamber - Rodrigo P. Feitosa; Johar Amin Ahmed Abdullah; Ramón R. Peña-Garcia; Maria G. Fonseca; Edson C. Silva-Filho; Santiago Medina-Carrasco; Maria del Mar Orta Cuevas; Josy A. Osajima (Chemical Engineering Journal, 2026)

Non-native mollusc species in Brazil: a first national inventory and distributional overview - Fabrizio Marcondes Machado; Rodrigo B. Salvador; Igor C. Miyahira; Luiz Ricardo Lopes de Simone; Tarcilla C. de Lima; Mariana Osório Côrtes; Julia D. Sigwart; Angie Patiño Montoya; Vanessa S. Amaral; Paula Spotorno; Marcel Sabino Miranda; Augusto L. Ferreira Júnior; et al. (Biological Invasions, 2026)

Correction: Partitioning Soil Respiration: Differentiating Root Contributions and Environmental Factors - Wanderson Benerval de Lucena; Daniel Carlos Machado; Polyana Pereira; Maria Elisa Vicentini; José A. Neira Román; Glauco de Sousa Rolim; Alan Rodrigo Panosso; Newton La Scala (Agricultural Research, 2026)

Spectroscopic exploration of mode of binding of ct DNA and BSA with acridone alkaloids isolated from Zanthoxylum leprieurii (Rutaceae) - Whistler Lucain Dibahteu Tankoua; Ernestine Zondegoumba T. Nkwengoua; Soh Desiré; Olivier Ndogo Eteme; Emmanuella Marthe Tchana Satchet; Rodrigo Santos A. de Araujo; Anuraj Nayarisseri; Maria do Carmo Alves de Lima; Thiago Mendonça de Aquino; Nyassé Barthélémy; Francisco J. B. Mendonça-Junior (Natural Product Research, 2026)

Potential of an entomopathogenic fungus from the Cladosporium cladosporioides species complex for aphid control: insights from biological parameters and bioassays - Carlos A. Silva; Liliana Godoy; Maria Isabel Ahumada; Mariajose Carvajal; Rodrigo A. Chorbadjian (BioControl, 2025)

A balanced approach to the potential of octopus aquaculture - Ian G. Gleadall; Roger Villanueva; Gregory J. Barord; Zoe Doubleday; Felipe Aguado-Giménez; Nobuhiko Akiyama; Eduardo Almansa; Cheryl L. Ames; Alexander Arkhipkin; Otilio Avendaño; Chris Barrett; Giambattista Bello; et al. (Marine Policy, 2025)

Reproductive outcomes of prepubertal Bos indicus beef heifers raised in a feedlot system submitted or not to ovulation induction strategies prior to a timed-artificial insemination treatment regimen - Rodrigo L.O.R. Alves; Lucas O. e Silva; Carlos E.C. Consentini; Oseias P. Santos; Andrés A.C. Narváez; Leandro D. da Cunha; Rafael A. Braz; Maria E.R. e Silva; Rodrigo Brüner; Leonardo F. Melo; Roberto Sartori (Theriogenology, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Soil carbon and nutrient stocks under intensified pasture and sugarcane expansion - Luiza Pecci Canisares; Eduardo Mariano; Adibe L. Abdalla-Filho; Lucas P. Canisares; Mauricio C. A. Leite; Maria G. S. Araújo; Rodrigo F. Almeida; Taciana F. Gomes; Érika S. P. B. Saldanha; Luiz A. Martinelli (Nutrient Cycling in Agroecosystems, 2025)

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Mitonuclear genetics reveals a novel perspective on the stock structure and fishery management of skipjack tuna (Katsuwonus pelamis) in the Atlantic Ocean - Maria Clara G. Queiroz-Brito; Fernando F. Mendonça; Joana I. Robalo; Freddy Arocha; N’Guessan Constance Diaha; Monin Justin Amandé; Fambaye Ngom Sow; Davy Angueko; Paulo Travassos; Rodrigo A. Torres (Reviews in Fish Biology and Fisheries, 2025)

Bird–window collisions: A comprehensive dataset for the Neotropical region - Augusto João Piratelli; Bianca Costa Ribeiro; Wesley Dáttilo; Luis‐Bernardo Vázquez; Anelisa Ferreira de Almeida Magalhães; Edna Maria Gomes Cavalcante; Eric Silva; Giovanna Viana Cruz; Gisele Regina Ruy; Juliana Laurito Summa; Júlia Milan; Leila Pedrosa; et al. (Ecology, 2025)
Our primary objective was to compile a comprehensive dataset on bird–window collisions throughout the Neotropical region, including both published and unpublished sources. On May 12, 2020, we extensively disseminated invitations to provide data via email and social media platforms. By providing a template worksheet, we required standardized information from collaborators to complete and register their data. To better understand how these data were acquired (e.g., incidental observations and systematic procedures), we sent out a survey to all collaborators. We established rigorous validation criteria for data inclusion and conducted thorough curation procedures to ensure accuracy. After the filtering process, we compiled a total of 4103 bird–window collision reports. These came from 11 Neotropical countries, dating from 1946 to 2020, and revealing distinct regional patterns and potential seasonal patterns. The five most frequent orders were Passeriformes (2451), Columbiformes (520), Apodiformes (377), Psittaciformes (202), and Piciformes (186). Data on bird–window collisions were collected through a local specific systematic protocol (1419), by chance (1252), by government agencies (742), and by other approaches (632), while a few reports were collected by unknown procedures (58). The volume of records across months in our dataset suggests that there may be temporal patterns, with peaks: the first one in March–April and the second one in October–November, which seem to align with the major migration and reproduction seasons. This dataset represents the first comprehensive effort in the Neotropical region focused on bird–window collision data, providing valuable insights for further scientific advancements and conservation policies. The data are free from copyright or proprietary restrictions. Please cite this data paper when using the data in publications or scientific presentations.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

LandFrag : A Dataset to Investigate the Effects of Forest Loss and Fragmentation on Biodiversity - Thiago Gonçalves‐Souza; Maurício Humberto Vancine; Nathan J. Sanders; Nick M. Haddad; Lucas Cortinhas; Anne Lene T. O. Aase; Willian Moura de Aguiar; Marcelo Adrian Aizen; Víctor Arroyo‐Rodríguez; Arturo Baz; Maíra Benchimol; Enrico Bernard; et al. (Global Ecology and Biogeography, 2025)
Motivation The accelerated and widespread conversion of once continuous ecosystems into fragmented landscapes has driven ecological research to understand the response of biodiversity to local (fragment size) and landscape (forest cover and fragmentation) changes. This information has important theoretical and applied implications, but is still far from complete. We compiled the most comprehensive and updated database to investigate how these local and landscape changes determine species composition, abundance and trait diversity of multiple taxonomic groups in forest fragments across the globe. Main Types of Variables Contained We gathered data for 1472 forest fragments, providing information on the abundance and composition of 9154 species belonging to vertebrates, invertebrates, and plants. For 2703 of these species, we obtained more than 20 functional traits. We provided the spatial location and size of each fragment and metrics of landscape composition and configuration. Spatial Location and Grain The dataset includes 1472 forest fragments sampled in 121 studies from all continents except Antarctica. Most datasets (77%) are from tropical regions, 17% are from temperate regions, and 6% are from subtropical regions. Species abundance and composition were collected at the plot or fragment scale, whereas the landscape metrics were extracted with buffer size ranging from a radius of 200–2000 m. Time Period and Grain Data on the abundance of species and community composition were collected between 1994 and 2022, and the landscape metrics were extracted from the same year that a given study collected the abundance and composition data. Major Taxa and Level of Measurement The studied organisms included invertebrates (Arachnida, Insecta and Gastropoda; 41% of the datasets), vertebrates (Amphibia, Squamata, Aves and Mammalia; 44%), and vascular plants (19%), and the lowest level of identification was species or morphospecies. Software Format The dataset and code can be downloaded on Zenodo or GitHub.

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Influence of carbon type in microbial communities formation when setting up BAC for secondary effluents treatment - Luan A. Camara; Rodrigo P. Cavalcante; Jacqueline A. Malvestiti; Maria J. dos Santos; Karina D. Pereira; Augusto D. Luchessi; Valdemar L. Tornisielo; Renato F. Dantas (Journal of Water Process Engineering, 2024)

Enteroaggregative Escherichia coli (EAEC) isolates obtained from non-diarrheic children carry virulence factor-encoding genes from Extraintestinal Pathogenic E. Coli (ExPEC) - Bruna M. Luiz; Maria C. Cergole-Novella; Stéfani T. A. Dantas; Daiany R. P. de Lira; Guilherme F. R. de Souza; Iranildo do A. Fernandes; Henrique Orsi; Guilherme Solveira; Vera L. M. Rall; Luís F. dos Santos; Rodrigo T. Hernandes (Brazilian Journal of Microbiology, 2024)

Pharmaceuticals in the environment: A strategy for prioritizing molecules of environmental concern - Taciana Guarnieri; Jacqueline R. Nascimento; Marcus Leonan; Pedro R. Brandão; Camilo Dias Seabra Pereira; Rodrigo Brasil Choueri; Elisa Hardt; Maria Lourdes L. Moraes; Leandro A. Calixto; Vanessa J. Pereira; Levi G. Oliveira; Sherlan Guimarães Lemos; et al. (Chemosphere, 2024)

A systematic review of the land use change effects on ant diversity in Neotropics - Icaro Wilker; Antônio C.M. Queiroz; Carla R. Ribas; Maria Santina C. Morini; Chaim J. Lasmar; Fernando A. Schmidt; Rodrigo M. Feitosa; Anselmo Nogueira; Fabrício B. Baccaro; Mônica A. Ulysséa; Thiago Izzo; Lucas N. Paolucci; et al. (Biological Conservation, 2024)

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Catalytic ozonation using spent battery-based (SB) catalysts for dyes, micropollutant removal and disinfection - Jacqueline A. Malvestiti; Maina Ruth C. Silva; Iure B. de Sousa; Rodrigo P. Cavalcante; Amanda Gondim C. Quirino; Guenther C.C. Viana; Elisângela Maria R. Rocha; Renato F. Dantas (Journal of Water Process Engineering, 2024)

Tropical forest succession increases tree taxonomic and functional richness but decreases evenness - Masha T. van der Sande; Lourens Poorter; Géraldine Derroire; Mario Marcos do Espirito Santo; Madelon Lohbeck; Sandra C. Müller; Radika Bhaskar; Michiel van Breugel; Juan Manuel Dupuy‐Rada; Sandra M. Durán; Catarina C. Jakovac; Horacio Paz; et al. (Global Ecology and Biogeography, 2024)
Aim Successional changes in functional diversity provide insights into community assembly by indicating how species are filtered into local communities based on their traits. Here, we assess successional changes in taxonomic and functional richness, evenness and redundancy along gradients of climate, soil pH and forest cover. Location Neotropics. Time period Last 0–100 years. Major taxa studied Trees. Methods We used 22 forest chronosequence studies and 676 plots across the Neotropics to analyse successional changes in Hill's taxonomic and functional diversity of trees, and how these successional changes vary with continental‐scale gradients in precipitation, soil pH and surrounding forest cover. Results Taxonomic and functional richness and functional redundancy increased, while taxonomic and functional evenness decreased over time. Functional richness and evenness changed strongly when not accounting for taxonomic richness, but changed more weakly after statistically accounting for taxonomic richness, indicating that changes in functional diversity are largely driven by taxonomic richness. Nevertheless, the successional increases in functional richness when correcting for taxonomic richness may indicate that environmental heterogeneity and limiting similarity increase during succession. The taxonomically‐independent successional decreases in functional evenness may indicate that stronger filtering and competition select for dominant species with similar trait values, while many rare species and traits are added to the community. Such filtering and competition may also lead to increased functional redundancy. The changes in taxonomically‐independent functional diversity varied with resource availability and were stronger in harsh, resource‐poor environments, but weak in benign, productive environments. Hence, in resource‐poor environments, environmental filtering and facilitation are important, whereas in productive environments, weaker abiotic filtering allows for high initial functional diversity and weak successional changes. Main conclusion We found that taxonomic and functional richness and functional redundancy increased and taxonomic and functional evenness decreased during succession, mainly caused by the increasing number of rare species and traits due to the arrival of new species and due to changing (a)biotic filters.

Mixed-marker data indicate the population biology, history, and the stock structure of crevalle jack Caranx hippos (Linnaeus, 1766) in the tropical Atlantic: A regional and latitudinal conservation genetics approach - Maria Clara G. Queiroz-Brito; Gabriela Rocha Defavari; Uedson Pereira Jacobina; Rodrigo A. Torres (Regional Studies in Marine Science, 2024)

Changes in submerged macrophyte diversity, coverage and biomass in a biosphere reserve site after 20 years: A plea for conservation efforts - Eric Puche; Daniel Cruz; Pilar Delgado; Joanna Rosińska; Maria A. Rodrigo (Biological Conservation, 2024)

Pressurized liquid extraction assisted by high-intensity ultrasound to obtain hesperidin from lime waste: Integration of in-line purification and on-line chromatographic analysis - Vitor L. Sanches; Monique Martins Strieder; Marcia Cristina Breitkreitz; Rosângela Maria Neves Bezerra; Jaísa O. Chaves; Isadora Lopes de Oliveira; Leonardo M. de Souza Mesquita; Juliane Viganó; Letícia Sanches Contieri; Rodrigo Stein Pizani; Maurício A. Rostagno (Food Research International, 2024)

Correction to: The Kelp Forest Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh‑Dalmau; Nina Larissa Arroyo; Anne M. Bauer‑Civiello; Rodrigo Beas‑Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)

The Kelp Forest ﻿Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh-Dalmau; Nina Larissa Arroyo; Anne M. Bauer-Civiello; Rodrigo Beas-Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)
Marine kelp forests cover 1/3 of our world's coastlines, are heralded as a nature-based solution to address socio-environmental issues, connect hundreds of millions of people with the ocean, and support a rich web of biodiversity throughout our oceans. But they are increasingly threatened with some areas reporting over 90% declines in kelp forest cover in living memory. Despite their importance and the threats they face, kelp forests are entirely absent from the international conservation dialogue. No international laws, policies, or targets focus on kelp forests and very few countries consider them in their national policy. The Kelp Forest Challenge addresses that gap. Together with 252 kelp experts, professionals, and citizens from 25 countries, the Kelp Forest Challenge was developed as a grassroots vision of what the world can achieve for kelp forest conservation. It is a global call to restore 1 million and protect 3 million hectares of kelp forests by 2040. This is a monumental challenge, that will require coordination across multiple levels of society and the mobilization of immense resources. Pledges may therefore include area for protection or restoration, enabling pledges which assist in conservation (funding, equipment, professional expertise, capacity building), or awareness-based pledges which increase awareness or education about kelp forests. Correspondingly, participants may be from government, scientific institutions, private sector, NGOs, community groups, or individuals. This challenge is the beginning of a 17-year mission to save our kelp forests and anyone and any organisation is invited to participate.

Exploring the potential of cellulose autofluorescence for optical detection of tannin in red wines - Kelcilene B.R. Teodoro; Maycon J. Silva; Rafaela S. Andre; Rodrigo Schneider; Maria A. Martins; Luiz H.C. Mattoso; Daniel S. Correa (Carbohydrate Polymers, 2024)

Groundwater is a hidden global keystone ecosystem - Mattia Saccò; Stefano Mammola; Florian Altermatt; Roman Alther; Rossano Bolpagni; Anton Brancelj; David Brankovits; Cene Fišer; Vasilis Gerovasileiou; Christian Griebler; Simone Guareschi; Grant C. Hose; et al. (Global Change Biology, 2024)
Groundwater is a vital ecosystem of the global water cycle, hosting unique biodiversity and providing essential services to societies. Despite being the largest unfrozen freshwater resource, in a period of depletion by extraction and pollution, groundwater environments have been repeatedly overlooked in global biodiversity conservation agendas. Disregarding the importance of groundwater as an ecosystem ignores its critical role in preserving surface biomes. To foster timely global conservation of groundwater, we propose elevating the concept of keystone species into the realm of ecosystems, claiming groundwater as a keystone ecosystem that influences the integrity of many dependent ecosystems. Our global analysis shows that over half of land surface areas (52.6%) has a medium‐to‐high interaction with groundwater, reaching up to 74.9% when deserts and high mountains are excluded. We postulate that the intrinsic transboundary features of groundwater are critical for shifting perspectives towards more holistic approaches in aquatic ecology and beyond. Furthermore, we propose eight key themes to develop a science‐policy integrated groundwater conservation agenda. Given ecosystems above and below the ground intersect at many levels, considering groundwater as an essential component of planetary health is pivotal to reduce biodiversity loss and buffer against climate change.

Functional responses in a lizard along a 3.5‐km altitudinal gradient - Nina Serén; Rodrigo Megía‐Palma; Tatjana Simčič; Miha Krofel; Fabio Maria Guarino; Catarina Pinho; Anamarija Žagar; Miguel A. Carretero (Journal of Biogeography, 2023)
Aim Physiological and metabolic performance are key mediators of the functional response of species to environmental change. Few environments offer such a multifaceted array of stressors as high‐altitude habitats, which differ markedly in temperature, water availability, UV radiation and oxygen pressure compared to low‐altitude habitats. Species that inhabit large altitudinal gradients are thus excellent models to study how organisms respond to environmental variation. Location Tenerife island, Canary Islands archipelago (Spain). Taxon Tenerife lizard ( Gallotia galloti , Lacertidae). Methods We integrated data on age structure, thermal and hydric regulatory behaviour and four metabolic and stress‐related biomarkers for an insular lizard that inhabits an extreme altitudinal range (sea level to 3700 m a.s.l.), to understand how an ectotherms' age, ecophysiology and metabolism can be affected by extreme environmental variation. Results We found marked differences in metabolic stress markers associated with altitude (particularly in the abundance of carbonyl metabolites and relative telomere length), but without a linear pattern along the altitudinal cline. Contrary to expectations, longer telomeres and lower carbonyl content were detected at the highest altitude, suggesting reduced stress in these populations. Evaporative water loss differed between populations but did not follow a linear altitudinal gradient. Lizard age structure or thermal physiological performance did not markedly change across different altitudes. Mixed signals in life‐history and thermal ecology across populations and altitude suggest complex responses to variable conditions across altitude in this species. Main Conclusions Our integrative study of multiple functional traits demonstrated that adaptation to highly divergent environmental conditions in this lizard is potentially linked to an interplay between plasticity and local adaptation variably associated with different functional traits.

How natural and anthropogenic factors should drive microplastic behavior and fate: The scenario of Brazilian urban freshwater - Fernando F. Sodré; Imisi M. Arowojolu; Maria C. Canela; Rodrigo S. Ferreira; Andreia N. Fernandes; Cassiana C. Montagner; Cristiane Vidal; Mariana A. Dias; Gilberto Abate; Leticia C. da Silva; Marco T. Grassi; Crislaine Bertoldi; et al. (Chemosphere, 2023)

Dirofilaria immitis in pet dogs from the metropolitan area of the Colombian Caribbean - Maria A. Badillo-Viloria; Ignacio García-Bocanegra; Rodrigo J. de Lavalle-Galvis; Remigio Martínez; Steffania de la Rosa-Jaramillo; Adriana Castillo-Castañeda; Juan D. Ramírez; David Cano-Terriza (Comparative Immunology, Microbiology and Infectious Diseases, 2023)

Rhomb-I, a P–I metalloproteinase from Lachesis muta rhombeata venom degrades vessel extra cellular matrix components and impairs platelet aggregation - Valéria Gonçalves de Alvarenga; Luciana S. Oliveira; Gustavo O. Santos; Dan E. Vivas-Ruiz; Márcia Helena Borges; Rodrigo C.G. de Souza; Johannes A. Eble; Ana Maria Moura-da-Silva; Eladio F. Sanchez (Toxicon, 2023)

Equine endometrial Th1 and Th2 evaluation during early pregnancy - Gustavo R Larentis; Henrique B A Bastos; Giovani C Camozzato; Maria N Martinez; Luiz A M Centeno; Verônica L C Bueno; Gustavo H Z Winter; Sandra Fiala-Rechsteiner; Rodrigo C Mattos (Journal of Equine Veterinary Science, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Species movements within biogeographic regions: exploring the distribution of transplanted mollusc species in South America - Gustavo Darrigran; Ignacio Agudo-Padrón; Pedro Baez; Carlos Belz; Franz Cardoso; Gonzalo A. Collado; Modesto Correoso; María Gabriela Cuezzo; Cristina Damborenea; Alejandra A. Fabres; Monica A. Fernandez; Suzete R. Gomes; et al. (Biological Invasions, 2023)

Improved remediation of contaminated water using ZnO systems via chemical treatment: applications, implications and toxicological mitigation - Josy A. Osajima; Alexandro S. Sá; Rodrigo P. Feitosa; Marcelo B. Furtini; Luzia M. C. Honorio; Maria G. Fonseca; Pollyana Trigueiro; Paula Caregnato; Eduardo R. Triboni; Edson C. Silva-Filho (Sustainable Water Resources Management, 2023)

Temporal variability of the CO2 emission and the O2 influx in a tropical soil in contrasting coverage conditions - Wanderson Benerval De Lucena; Maria Elisa Vicentini; Gustavo André De Araújo Santos; Bruna De Oliveira Silva; Daniel Vítor Mesquita Da Costa; Kleve Freddy Ferreira Canteral; José A. Neira Román; Glauco De Souza Rolim; Alan Rodrigo Panosso; Newton La Scala Jr (Journal of South American Earth Sciences, 2023)

Natural lignin modulators improve lignocellulose saccharification of field-grown sugarcane, soybean, and brachiaria - Wanderley D. dos Santos; Diego E.R. Gonzaga; Victor Hugo Salvador; Denis L. Freitas; Breno M. Joia; Dyoni M. Oliveira; Débora C.C. Leite; Graciene S. Bido; Aline Finger-Teixeira; Amanda P. de Souza; Maria de Lourdes T.M. Polizeli; Rodrigo P. Constantin; et al. (Biomass and Bioenergy, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Rock n' Seeds: A database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation - Carlos A. Ordóñez‐Parra; Roberta L. C. Dayrell; Daniel Negreiros; Antônio C. S. Andrade; Letícia G. Andrade; Yasmine Antonini; Leilane C. Barreto; Fernanda de V. Barros; Vanessa da Cruz Carvalho; Blanca Auxiliadora Dugarte Corredor; Antônio Cláudio Davide; Alexandre A. Duarte; et al. (Ecology, 2023)
Advancing functional ecology depends fundamentally on the availability of data on reproductive traits, including those from tropical plants, which have been historically underrepresented in global trait databases. Although some valuable databases have been created recently, they are mainly restricted to temperate areas and vegetative traits such as leaf and wood traits. Here, we present Rock n' Seeds, a database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation, recognized as outstanding centers of diversity and endemism. Data were compiled through a systematic literature search, resulting in 103 publications from which seed functional traits were extracted. The database includes information on 16 functional traits for 383 taxa from 148 genera, 50 families, and 25 orders. These 16 traits include two dispersal, six production, four morphological, two biophysical, and two germination traits—the major axes of the seed ecological spectrum. The database also provides raw data for 48 germination experiments, for a total of 10,187 records for 281 taxa. Germination experiments in the database assessed the effect of a wide range of abiotic and biotic factors on germination and different dormancy‐breaking treatments. Notably, 8255 of these records include daily germination counts. This input will facilitate synthesizing germination data and using this database for a myriad of ecological questions. Given the variety of seed traits and the extensive germination information made available by this database, we expect it to be a valuable resource advancing comparative functional ecology and guiding seed‐based restoration and biodiversity conservation in tropical megadiverse ecosystems. There are no copyright restrictions on the data; please cite this paper when using the current data in publications; also the authors would appreciate notification of how the data are used in publications.

Ants of Brazil: an overview based on 50 years of diversity studies - Rodrigo M. Feitosa; Gabriela P. Camacho; Thiago S. R. Silva; Mônica A. Ulysséa; Natalia Ladino; Aline M. Oliveira; Emília Z. Albuquerque; Fernando A. Schmidt; Carla R. Ribas; Anselmo Nogueira; Fabrício B. Baccaro; Antônio C. M. Queiroz; et al. (Systematics and Biodiversity, 2022)

Two constructed wetlands within a Mediterranean natural park immersed in an agrolandscape reduce most heavy metal water concentrations and dampen the majority of pesticide presence - Maria A. Rodrigo; Eric Puche; Nuria Carabal; Sergio Armenta; Francesc A. Esteve-Turrillas; Javier Jiménez; Fernando Juan (Environmental Science and Pollution Research, 2022)
The water concentrations of 12 heavy and other metals/metalloids were analyzed seasonally along two horizontal-flow constructed wetlands (CWs) (Tancat Mília—TM and Tancat l’Illa—TLI) located within the Mediterranean Albufera de València Natural Park during 2020–2021. A wide-scope screening of pesticides present in waters was also performed. The two CWs were created to improve water quality and increase biodiversity. They currently receive effluent waters from two different tertiary-treatment wastewater plants, and the water flows along the CWs before being discharged into the main lagoon and a smaller lagoon in TM and TLI, respectively. TLI manages to reduce (Mn) or maintain the concentration of most of the studied elements (Zn, Ni, Hg, Cr, Fe Cd, Cu) at the same level as outside (67%). Only Al, Pb, B, and As remain at a higher concentration. TM also reduces Zn and Cu and keeps the concentration of Cr, Cd, and Hg (representing 42%). Al, Pb, B, and As remain at higher concentrations, as in TLI, but Ni, Fe, and Mn are also at higher concentrations. Although both CWs vary in their ability to remove elements, no risks to human health or the environment have been detected due to the low metal concentration in their outlets, all of them (except Hg) below the legal limits for environmental quality in the European Union. With the detection of 71 compounds in water in each CW area (26 herbicides, 26 insecticides, and 19 fungicides in TLI, and 29 herbicides, 23 insecticides, and 19 fungicides in TM), we also provide evidence of the impact of pesticides, which depends on the application method (helicopter, tractor), originated from areas with high agricultural pressure (chiefly rice crops) on systems (mainly TM) created to preserve biodiversity. Nevertheless, both systems provide crucial environmental services in water quality in this agrolandscape.

Performance of Sentinel-2 SAFER ET model for daily and seasonal estimation of grapevine water consumption - Anderson L. S. Safre; Ayman Nassar; Alfonso Torres-Rua; Mayhar Aboutalebi; João C. C. Saad; Rodrigo L. Manzione; Antonio Heriberto de Castro Teixeira; John H. Prueger; Lynn G. McKee; Joseph G. Alfieri; Lawrence E. Hipps; Hector Nieto; et al. (Irrigation Science, 2022)

Uniparental markers reveal new insights on subcontinental ancestry and sex-biased admixture in Brazil - Iriel A. Joerin-Luque; Danillo G. Augusto; Verónica Calonga-Solís; Rodrigo Coutinho de Almeida; Claudemira Vieira Gusmão Lopes; Maria Luiza Petzl-Erler; Marcia Holsbach Beltrame (Molecular Genetics and Genomics, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

The microbiome of a shell mound: ancient anthropogenic waste as a source of Streptomyces degrading recalcitrant polysaccharides - Luciano F. Huergo; Marcelo Conzentino; Maria V. Gonçalves; Marcos V. Gernet; Rodrigo A. Reis; Fábio O. Pedrosa; Valter A. Baura; Araceli Pires; Edileusa C. M. Gerhardt; Thalita R. Tuleski; Eduardo Balsanelli; Dieval Guizelini; et al. (World Journal of Microbiology and Biotechnology, 2021)

Pyramiding dsRNAs increases phytonematode tolerance in cotton plants - Maria E. Lisei-de-Sá; Paolo L. Rodrigues-Silva; Carolina V. Morgante; Bruno Paes de Melo; Isabela T. Lourenço-Tessutti; Fabricio B. M. Arraes; João P. A. Sousa; Rafael Galbieri; Regina M. S. Amorim; Camila B. J. de Lins; Leonardo L. P. Macedo; Valdeir J. Moreira; et al. (Planta, 2021)

Correction to: Reproducibility and accuracy of microscale thermophoresis in the NanoTemper Monolith: a multi laboratory benchmark study - Blanca López-Méndez; Bruno Baron; Chad A. Brautigam; Thomas A. Jowitt; Stefan H. Knauer; Stephan Uebel; Mark A. Williams; Arthur Sedivy; Olga Abian; Celeste Abreu; Malgorzata Adamczyk; Wojciech Bal; et al. (European Biophysics Journal, 2021)

LT‐Brazil: A database of leaf traits across biomes and vegetation types in Brazil - Eduardo Mariano; Taciana F. Gomes; Silvia R. M. Lins; Adibe L. Abdalla‐Filho; Amin Soltangheisi; Maria G. S. Araújo; Rodrigo F. Almeida; Fernanda G. Augusto; Luiza P. Canisares; Siglea S. F. Chaves; Cristiane F. G. Costa; Thaís R. Diniz‐Reis; et al. (Global Ecology and Biogeography, 2021)
Motivation Leaf traits represent an important component of plant functional strategies, and those related to carbon fixation and nutrient acquisition form the leaf economics spectrum. However, observations of functional leaf traits are underrepresented in tropical regions in comparison with those in temperate areas. Brazil, a country with continental scale and vast biodiversity is a timely example, where many biomes are impacted by human activities and climate change. However, leaf traits relevant to understand vegetation responses to these impacts remain poorly quantified for many species found in the country. We compiled an extensive data set of four functional leaf traits for native woody species occurring in the Brazilian territory. In addition to trait observations, sampling dates and geo‐references were compiled and climatic parameters and soil properties of each sampling site were extracted from several databases. Main types of variables contained The LT‐Brazil data set contains 3,479, 1,216, 775 and 775 clean observations of leaf mass per area, leaf nitrogen (N) concentration per unit mass, leaf phosphorus (P) concentration per unit mass, and leaf N : P ratio, respectively, from native woody species, encompassing information of biome, vegetation, taxonomic data, geographical coordinates, climatic parameters, as well as soil properties. Spatial location and grain We compiled trait observations from 223 sites under native vegetation distributed in all main biomes (i.e., Amazônia, Caatinga, Cerrado, Mata Atlântica, Pampa and Pantanal) across the Brazilian territory. Time period and grain The data represent information published and/or sampled during the last 25 years. Major taxa and level of measurement Our compilation was focused on trait data observed for native woody species, excluding monocots, palm trees, herbs, and hemiparasitic plants. Thus, 108, 478 and 1,321 botanical families, genera and species were included, covering c . 9% of the woody angiosperm flora of Brazil. Software format Data are provided as comma‐separated value (.csv) files.

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Reproducibility and accuracy of microscale thermophoresis in the NanoTemper Monolith: a multi laboratory benchmark study - Blanca López-Méndez; Bruno Baron; Chad A. Brautigam; Thomas A. Jowitt; Stefan H. Knauer; Stephan Uebel; Mark A. Williams; Arthur Sedivy; Olga Abian; Celeste Abreu; Malgorzata Adamczyk; Wojciech Bal; et al. (European Biophysics Journal, 2021)
Microscale thermophoresis (MST), and the closely related Temperature Related Intensity Change (TRIC), are synonyms for a recently developed measurement technique in the field of biophysics to quantify biomolecular interactions, using the (capillary-based) NanoTemper Monolith and (multiwell plate-based) Dianthus instruments. Although this technique has been extensively used within the scientific community due to its low sample consumption, ease of use, and ubiquitous applicability, MST/TRIC has not enjoyed the unambiguous acceptance from biophysicists afforded to other biophysical techniques like isothermal titration calorimetry (ITC) or surface plasmon resonance (SPR). This might be attributed to several facts, e.g., that various (not fully understood) effects are contributing to the signal, that the technique is licensed to only a single instrument developer, NanoTemper Technology, and that its reliability and reproducibility have never been tested independently and systematically. Thus, a working group of ARBRE-MOBIEU has set up a benchmark study on MST/TRIC to assess this technique as a method to characterize biomolecular interactions. Here we present the results of this study involving 32 scientific groups within Europe and two groups from the US, carrying out experiments on 40 Monolith instruments , employing a standard operation procedure and centrally prepared samples. A protein–small molecule interaction, a newly developed protein–protein interaction system and a pure dye were used as test systems. We characterized the instrument properties and evaluated instrument performance, reproducibility, the effect of different analysis tools, the influence of the experimenter during data analysis, and thus the overall reliability of this method.

Cytotoxicity of glucoevatromonoside alone and in combination with chemotherapy drugs and their effects on Na+,K+-ATPase and ion channels on lung cancer cells - Naira Fernanda Zanchett Schneider; Danusa Menegaz; Andre Luiz Andreotti Dagostin; Lara Persich; Sayonarah C. Rocha; Ana Carolina Pacheco Ramos; Vanessa Faria Cortes; Carlos Frederico Leite Fontes; Rodrigo Maia de Pádua; Jennifer Munkert; Wolfgang Kreis; Fernão Castro Braga; et al. (Molecular and Cellular Biochemistry, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Sustained mass coral bleaching (2016–2017) in Brazilian turbid-zone reefs: taxonomic, cross-shelf and habitat-related trends - Carolina D. Teixeira; Rodrigo L. L. Leitão; Felipe V. Ribeiro; Fernando C. Moraes; Leonardo M. Neves; Alex C. Bastos; Guilherme H. Pereira-Filho; Milton Kampel; Paulo S. Salomon; João A. Sá; Ludmilla N. Falsarella; Michelle Amario; et al. (Coral Reefs, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Effects of dietary supplementation of Gracilaria sp. extracts on fillet quality, oxidative stress, and immune responses in European seabass (Dicentrarchus labrax) - Maria J. Peixoto; Leonardo Magnoni; José F. M. Gonçalves; Robert H. Twijnstra; Anake Kijjoa; Rui Pereira; Arjan P. Palstra; Rodrigo O. A. Ozório (Journal of Applied Phycology, 2019)

ATLANTIC ‐ PRIMATES : a dataset of communities and occurrences of primates in the Atlantic Forests of South America - Laurence Culot; Lucas Augusto Pereira; Ilaria Agostini; Marco Antônio Barreto de Almeida; Rafael Souza Cruz Alves; Izar Aximoff; Alex Bager; María Celia Baldovino; Thiago Ribas Bella; Júlio César Bicca‐Marques; Caryne Braga; Carlos Rodrigo Brocardo; et al. (Ecology, 2019)
Primates play an important role in ecosystem functioning and offer critical insights into human evolution, biology, behavior, and emerging infectious diseases. There are 26 primate species in the Atlantic Forests of South America, 19 of them endemic. We compiled a dataset of 5,472 georeferenced locations of 26 native and 1 introduced primate species, as hybrids in the genera Callithrix and Alouatta . The dataset includes 700 primate communities, 8,121 single species occurrences and 714 estimates of primate population sizes, covering most natural forest types of the tropical and subtropical Atlantic Forest of Brazil, Paraguay and Argentina and some other biomes. On average, primate communities of the Atlantic Forest harbor 2 ± 1 species (range = 1–6). However, about 40% of primate communities contain only one species. Alouatta guariba (N = 2,188 records) and Sapajus nigritus (N = 1,127) were the species with the most records. Callicebus barbarabrownae (N = 35), Leontopithecus caissara (N = 38), and Sapajus libidinosus (N = 41) were the species with the least records. Recorded primate densities varied from 0.004 individuals/km 2 ( Alouatta guariba at Fragmento do Bugre, Paraná, Brazil) to 400 individuals/km 2 ( Alouatta caraya in Santiago, Rio Grande do Sul, Brazil). Our dataset reflects disparity between the numerous primate census conducted in the Atlantic Forest, in contrast to the scarcity of estimates of population sizes and densities. With these data, researchers can develop different macroecological and regional level studies, focusing on communities, populations, species co‐occurrence and distribution patterns. Moreover, the data can also be used to assess the consequences of fragmentation, defaunation, and disease outbreaks on different ecological processes, such as trophic cascades, species invasion or extinction, and community dynamics. There are no copyright restrictions. Please cite this Data Paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Effects of hybridization on sea turtle fitness - Luciano S. Soares; Karen A. Bjorndal; Alan B. Bolten; Maria A. G. dei Marcovaldi; Pedro B. Luz; Rodrigo Machado; Rachel Lo; Stuart F. McDaniel; Adam C. Payton; Thomas B. Waltzek; Marta L. Wayne (Conservation Genetics, 2018)

Biodiversity and climate determine the functioning of Neotropical forests - Lourens Poorter; Masha T. van der Sande; Eric J. M. M. Arets; Nataly Ascarrunz; Brian Enquist; Bryan Finegan; Juan Carlos Licona; Miguel Martínez‐Ramos; Lucas Mazzei; Jorge A. Meave; Rodrigo Muñoz; Christopher J. Nytch; et al. (Global Ecology and Biogeography, 2018)

Biodiversity and climate determine the functioning of Neotropical forests - Lourens Poorter; Masha T. van der Sande; Eric J. M. M. Arets; Nataly Ascarrunz; Brian J. Enquist; Bryan Finegan; Juan Carlos Licona; Miguel Martínez‐Ramos; Lucas Mazzei; Jorge A. Meave; Rodrigo Muñoz; Christopher J. Nytch; et al. (Global Ecology and Biogeography, 2017)
Aim Tropical forests account for a quarter of the global carbon storage and a third of the terrestrial productivity. Few studies have teased apart the relative importance of environmental factors and forest attributes for ecosystem functioning, especially for the tropics. This study aims to relate aboveground biomass (AGB) and biomass dynamics (i.e., net biomass productivity and its underlying demographic drivers: biomass recruitment, growth and mortality) to forest attributes (tree diversity, community‐mean traits and stand basal area) and environmental conditions (water availability, soil fertility and disturbance). Location Neotropics. Methods We used data from 26 sites, 201 1‐ha plots and >92,000 trees distributed across the Neotropics. We quantified for each site water availability and soil total exchangeable bases and for each plot three key community‐weighted mean functional traits that are important for biomass stocks and productivity. We used structural equation models to test the hypothesis that all drivers have independent, positive effects on biomass stocks and dynamics. Results Of the relationships analysed, vegetation attributes were more frequently associated significantly with biomass stocks and dynamics than environmental conditions (in 67 vs. 33% of the relationships). High climatic water availability increased biomass growth and stocks, light disturbance increased biomass growth, and soil bases had no effect. Rarefied tree species richness had consistent positive relationships with biomass stocks and dynamics, probably because of niche complementarity, but was not related to net biomass productivity. Community‐mean traits were good predictors of biomass stocks and dynamics. Main conclusions Water availability has a strong positive effect on biomass stocks and growth, and a future predicted increase in (atmospheric) drought might, therefore, potentially reduce carbon storage. Forest attributes, including species diversity and community‐weighted mean traits, have independent and important relationships with AGB stocks, dynamics and ecosystem functioning, not only in relatively simple temperate systems, but also in structurally complex hyper‐diverse tropical forests.

ATLANTIC ‐ CAMTRAPS : a dataset of medium and large terrestrial mammal communities in the Atlantic Forest of South America - Fernando Lima; Gabrielle Beca; Renata L. Muylaert; Clinton N. Jenkins; Miriam L. L. Perilli; Ana Maria O. Paschoal; Rodrigo L. Massara; Adriano P. Paglia; Adriano G. Chiarello; Maurício E. Graipel; Jorge J. Cherem; André L. Regolin; et al. (Ecology, 2017)
Our understanding of mammal ecology has always been hindered by the difficulties of observing species in closed tropical forests. Camera trapping has become a major advance for monitoring terrestrial mammals in biodiversity rich ecosystems. Here we compiled one of the largest datasets of inventories of terrestrial mammal communities for the Neotropical region based on camera trapping studies. The dataset comprises 170 surveys of medium to large terrestrial mammals using camera traps conducted in 144 areas by 74 studies, covering six vegetation types of tropical and subtropical Atlantic Forest of South America (Brazil and Argentina), and present data on species composition and richness. The complete dataset comprises 53,438 independent records of 83 species of mammals, includes 10 species of marsupials, 15 rodents, 20 carnivores, eight ungulates and six armadillos. Species richness averaged 13 species (±6.07 SD ) per site. Only six species occurred in more than 50% of the sites: the domestic dog Canis familiaris , crab‐eating fox Cerdocyon thous , tayra Eira barbara , south American coati Nasua nasua , crab‐eating raccoon Procyon cancrivorus and the nine‐banded armadillo Dasypus novemcinctus . The information contained in this dataset can be used to understand macroecological patterns of biodiversity, community, and population structure, but also to evaluate the ecological consequences of fragmentation, defaunation, and trophic interactions.

Labeling of adipose-derived stem cells with quantum dots provides stable and long-term fluorescent signal for ex vivo cell tracking - Clautina R. M. Costa; Matheus L. T. Feitosa; Dayseanny O. Bezerra; Yulla K. P. Carvalho; Rodrigo F. G. Olivindo; Pablo B. Fernando; Gustavo C. Silva; Mirna L. G. Silva; Carlos E. Ambrósio; Airton M. Conde Júnior; Napoleão M. Argolo Neto; Laís M. Costa Silva; et al. (In Vitro Cellular & Developmental Biology - Animal, 2017)

Interleukin-1 Receptor Antagonist Decreases Hypothalamic Oxidative Stress During Experimental Sepsis - Fazal Wahab; Nilton N. Santos-Junior; Rodrigo Pereira de Almeida Rodrigues; Luis Henrique A. Costa; Carlos Henrique R. Catalão; Maria Jose A. Rocha (Molecular Neurobiology, 2016)

Diets supplemented with seaweed affect metabolic rate, innate immune, and antioxidant responses, but not individual growth rate in European seabass (Dicentrarchus labrax) - Maria J. Peixoto; Jon C. Svendsen; Hans Malte; Luis F. Pereira; Pedro Carvalho; Rui Pereira; José F. M. Gonçalves; Rodrigo O. A. Ozório (Journal of Applied Phycology, 2016)

Genetic background of novel sequence types of CTX-M-8- and CTX-M-15-producing Escherichia coli and Klebsiella pneumoniae from public wastewater treatment plants in São Paulo, Brazil - Milena Dropa; Nilton Lincopan; Livia C. Balsalobre; Danielle E. Oliveira; Rodrigo A. Moura; Miriam Rodriguez Fernandes; Quézia Moura da Silva; Glavur R. Matté; Maria I. Z. Sato; Maria H. Matté (Environmental Science and Pollution Research, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Inhibition of cyclin-dependent kinase CDK1 by oxindolimine ligands and corresponding copper and zinc complexes - Rodrigo Bernardi Miguel; Philippe Alexandre Divina Petersen; Fernando A. Gonzales-Zubiate; Carla Columbano Oliveira; Naresh Kumar; Rafael Rodrigues do Nascimento; Helena Maria Petrilli; Ana Maria da Costa Ferreira (JBIC Journal of Biological Inorganic Chemistry, 2015)

Marker-trait association and epistasis for brown rust resistance in sugarcane - Fernanda R. C. Santos; Luciana R. Pinto; Luciana A. Carlini-Garcia; Rodrigo Gazaffi; Melina C. Mancini; Bruna S. Gonçalves; Cibele N. F. Medeiros; Dilermando Perecin; Antônio A. F. Garcia; Anete P. Souza; Maria I. Zucchi (Euphytica, 2015)

D-serine plasma concentration is a potential biomarker of (R,S)-ketamine antidepressant response in subjects with treatment-resistant depression - Ruin Moaddel; David A. Luckenbaugh; Ying Xie; Alma Villaseñor; Nancy E. Brutsche; Rodrigo Machado-Vieira; Anuradha Ramamoorthy; Maria Paz Lorenzo; Antonia Garcia; Michel Bernier; Marc C. Torjman; Coral Barbas; et al. (Psychopharmacology, 2015)

A model for quantitative trait loci mapping, linkage phase, and segregation pattern estimation for a full-sib progeny - Rodrigo Gazaffi; Gabriel R. A. Margarido; Maria Marta Pastina; Marcelo Mollinari; Antonio Augusto F. Garcia (Tree Genetics & Genomes, 2014)

The São Paulo shelf (SE Brazil) as a nursery ground for Doryteuthis plei (Blainville, 1823) (Cephalopoda, Loliginidae) paralarvae: a Lagrangian particle-tracking Individual-Based Model approach - Rodrigo Silvestre Martins; Ricardo de Camargo; Maria A. Gasalla (Hydrobiologia, 2014)

Transcriptional Profiles of Roots of Different Soybean Genotypes Subjected to Drought Stress - Renata Stolf-Moreira; Eliana G. M. Lemos; Lúcia Carareto-Alves; Jackson Marcondes; Selma S. Pereira; Amanda A. P. Rolla; Rodrigo M. Pereira; Norman Neumaier; Eliseu Binneck; Ricardo V. Abdelnoor; Maria C. N. de Oliveira; Francismar C. Marcelino; et al. (Plant Molecular Biology Reporter, 2011)

Serological Evidence of Paracoccidioides brasiliensis Infection in Chickens from Paraná and Mato Grosso do Sul States, Brazil - Gabriela G. Oliveira; Luciane H. Silveira; Eiko N. Itano; Rodrigo M. Soares; Roberta L. Freire; Maria A. E. Watanabe; Zoilo P. Camargo; Mario A. Ono (Mycopathologia, 2011)

Sustained primary production with changing phytoplankton assemblages in a semiarid wetland - Carmen Rojo; Maria Mercedes Barón-Rodríguez; Miguel Álvarez-Cobelas; Maria A. Rodrigo (Hydrobiologia, 2010)

Improved Enrichment and Isolation of Polycyclic Aromatic Hydrocarbons (PAH)-Degrading Microorganisms in Soil Using Anthracene as a Model PAH - Rodrigo J. S. Jacques; Benedict C. Okeke; Fátima M. Bento; Maria C. R. Peralba; Flávio A. O. Camargo (Current Microbiology, 2009)

Guarana (Paullinia cupana var. sorbilis), an anciently consumed stimulant from the Amazon rain forest: the seeded-fruit transcriptome - Paula C. S. Ângelo; Carlos G. Nunes-Silva; Marcelo M. Brígido; Juliana S. N. Azevedo; Enedina N. Assunção; Alexandra R. B. Sousa; Fernando J. B. Patrício; Mailson M. Rego; Jean C. C. Peixoto; Waldesse P. Oliveira; Danival V. Freitas; Elionor R. P. Almeida; et al. (Plant Cell Reports, 2008)

Hepatic morphological alterations, glycogen content and cytochrome P450 activities in rats treated chronically with Nω-nitro-L-arginine methyl ester (L-NAME) - Christiane Aparecida Badin Tarsitano; Valdemar A. Paffaro; José Rodrigo Pauli; Gustavo Henrique da Silva; Mario J. Saad; Ione Salgado; Maria Alice da Cruz-Höfling; Stephen Hyslop (Cell and Tissue Research, 2007)

Does seston size structure reflect fish-mediated effects on water quality in a degraded semiarid wetland? - David G. Angeler; Salvador Sánchez-Carrillo; Maria A. Rodrigo; Miguel Alvarez-Cobelas; Carmen Rojo (Environmental Monitoring and Assessment, 2007)

On the Importance of Water Depth, Macrophytes and Fish in Wetland Picocyanobacteria Regulation - David G. Angeler; Salvador Sánchez-Carrillo; Maria A. Rodrigo; Olga Viedma; Miguel Alvarez-Cobelas (Hydrobiologia, 2005)

Ticks (Acari: Ixodida) on wild carnivores in Brazil - Marcelo B. Labruna; Rodrigo S. P. Jorge; Dênis A. Sana; Anah Tereza A. Jácomo; Cyntia K. Kashivakura; Mariana M. Furtado; Claudia Ferro; Samuel A. Perez; Leandro Silveira; Tarcísio S. Santos JR; Samuel R. Marques; Ronaldo G. Morato; et al. (Experimental and Applied Acarology, 2005)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)